Technological innovation management as a factor of promotion up in venezuelan private universities (2017)
The purpose was to analyze the management of technological innovation as a factor for promoting entrepreneurship in Venezuelan private universities. Positivist research and experimental transectional not descriptive, field based on population census managers and university students last academic year for research projects. He used Likert questionnaire whose reliability Cronbach's alpha yielded results of 0.97 and 0.95 in in college students managers. It is concluded that should rise indicators of technological activity management and models of technology transfer to the university environment, by motivating students and inclusion in calls for innovation projects.